Boosting the Photoluminescence of Monolayer MoS2 on High‐Density Nanodimer Arrays with Sub‐10 nm Gap. Issue 2 (18th December 2017) - Hao, Qi; Pang, Jinbo; Zhang, Yang; Wang, Jiawei; Ma, Libo; Schmidt, Oliver G.
Abstract: Patterned plasmonic nanodimers are fabricated exploiting an ultrathin porous anodic aluminum oxide membrane as a mask during angle‐resolved shadow deposition. The fabricated nanodimer arrays exhibit consistent sub‐10 nm gaps and a high particle density up to 1.0 × 10 10 cm −2 over a large area. The ultrasmall dimer gaps provide highly confined electromagnetic fields, which strongly enhance the photoluminescence (PL) emission and Raman scattering from the surrounding monolayer molybdenum disulphide (MoS2 ). The ensemble PL intensity from MoS2 /dimers is enhanced by up to a factor of ≈160 by resonant excitation of the dimer modes. Anisotropic polarization‐dependent characteristics of PL and Raman from the MoS2 /dimers confirm that the dominant enhancement originates from the dimer configuration. These experiments demonstrate a facile approach for the fabrication of low‐cost high‐performance 2D material‐based optoelectronic devices. Abstract : Patterned dimers with consistent sub‐10 nm gaps and a high particle density up to 1.0 × 10 10 cm −2 are fabricated by utilizing an ultrathin anodic aluminum oxide membrane. The ensemble photoluminescence emission from molybdenum disulphide (MoS2 ) is enhanced by 160‐fold due to strongly confined electromagnetic fields from the dimers, and polarization‐dependent characteristics from MoS2 /dimers are revealed.